Designing tasks for the communicative classroom - Nunan, David (Cambridge Univ. Press, 1989)
The book is a balanced introduction to the theoretical and practical aspects of communicative task design. It addresses the essential components of a communicative task; the relationship between task design, curriculum development, syllabus design and methodology; recent research about the nature of listening, speaking, reading and writing; ...